2012
DOI: 10.1186/1756-0500-5-703
|View full text |Cite
|
Sign up to set email alerts
|

Health-related locus of control and health behaviour among university students in North Rhine Westphalia, Germany

Abstract: BackgroundHealth control beliefs were postulated to be associated with health behaviour. However, the results of studies assessing these associations suggest that they might not be universal. Among young adults associations have been reported, but the evidence is limited. The objective of this analysis was to re-examine these associations in a sample of university students in Germany.FindingsData from a multicentre cross-sectional study among university students in North Rhine-Westphalia, Germany was used (N=3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
4
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 31 publications
8
70
4
8
Order By: Relevance
“…In research conducted by Szczepańska and Lipowski, [24] of 470 people from the province of Pomorskie, it was shown that respondents with a greater indicator of internal locus of control health rated well above their health and physical condition. Confirmation of these results can be found in studies by Helmer et al [25], researching health and behaviour of health among people living in the Rhineland (Germany), and in research by Aflakseir and ZarrinPour [26], studying patients with type 2 diabetes. The research demonstrated that a greater sense of responsibility for their own health is associated with an internal locus of health control.…”
Section: Discussionsupporting
confidence: 64%
“…In research conducted by Szczepańska and Lipowski, [24] of 470 people from the province of Pomorskie, it was shown that respondents with a greater indicator of internal locus of control health rated well above their health and physical condition. Confirmation of these results can be found in studies by Helmer et al [25], researching health and behaviour of health among people living in the Rhineland (Germany), and in research by Aflakseir and ZarrinPour [26], studying patients with type 2 diabetes. The research demonstrated that a greater sense of responsibility for their own health is associated with an internal locus of health control.…”
Section: Discussionsupporting
confidence: 64%
“…Daugelis tyrėjų pripažįs-ta, kad besaikis alkoholio vartojimas, kai išgeriami dideli alkoholio kiekiai vienu metu (angl. binge drinking) ypač būdingas studentams (Ansari & Stock, 2010;Arnett, 2007;French & Cooke, 2012;Helmer, Kramer, & Mikolajczyk, 2012).…”
Section: Rezultatų Aptarimasunclassified
“…A literature review showed that one or two types of risky behaviour are tested in the surveys, not taking into account the confirmation about the covariance of risky behaviours (Duberstein-Lindberg et al, 2000;Jessor & Jessor, 1977;Monahan & Hawkins, 2009). We have to state that scientists and practitioners are more focused on secondary schools and adolescents in their research than on university students.…”
Section: Interrelations Of Risky Behavior and Sensation Seeking In Thmentioning
confidence: 99%
“…Research on health behaviors and their determinants has been quite selective in terms of mainly focusing either on external environmental factors or internal individual determinants of behavior; for instance, while studies have shown that external influences such as modeling may be very important in the context of smoking or drinking behavior (e.g., Sancho, Miguel, & Aldás, 2011;White, Johnson, & Buyske, 2000), internal determinants such as locus of control seem to have crucial importance in the context of engagement in physical activity or healthy eating (e.g., Helmer, Kramer, & Mikolajczyk, 2012). Certainly, the consideration of personal and environmental variables separately constitutes a major limitation to the proper understanding of the overall context in which health behaviors are established.…”
Section: Health Behaviors and The Problem-behavior Theory (Pbt)mentioning
confidence: 99%